2019
DOI: 10.1111/den.13414
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the factors involved in procedural failure: Endoscopic retrograde cholangiopancreatography using a short‐type single‐balloon enteroscope for patients with surgically altered gastrointestinal anatomy

Abstract: Aim To analyze factors involved in procedural failure and to discuss responses to procedural failure by using the outcomes of endoscopic retrograde cholangiopancreatography (ERCP) carried out using a short‐type single‐balloon enteroscope (short SBE) in patients with surgically altered gastrointestinal anatomy. Methods The study sample included patients who underwent ERCP‐related procedures using a short SBE between September 2011 and September 2018 at our hospital. Outcomes, including procedural success rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 29 publications
(59 reference statements)
1
57
1
Order By: Relevance
“…Only one retrospective study [39] compared long-type, not short-type, single and double balloon endoscopes for ERCP, and demonstrated similar outcomes between two scopes. Recently, two studies [38,40] reported clinical outcomes of a short-type single balloon endoscope for ERCP with technical success rates of 81.8 % and 85.9 % and AE rates of 5.9 % and 8.4 %, respectively, which is comparable to our study results. Although there were no studies comparing two short-type balloon endoscopes, it is reasonable to say the type of balloon endoscopes can be selected depending on the local expertise.…”
Section: Methodssupporting
confidence: 90%
“…Only one retrospective study [39] compared long-type, not short-type, single and double balloon endoscopes for ERCP, and demonstrated similar outcomes between two scopes. Recently, two studies [38,40] reported clinical outcomes of a short-type single balloon endoscope for ERCP with technical success rates of 81.8 % and 85.9 % and AE rates of 5.9 % and 8.4 %, respectively, which is comparable to our study results. Although there were no studies comparing two short-type balloon endoscopes, it is reasonable to say the type of balloon endoscopes can be selected depending on the local expertise.…”
Section: Methodssupporting
confidence: 90%
“…In patients with SAA who have undergone Whipple reconstruction and other procedures after PD, the rendezvous technique is mainly carried out to treat stricture of the PD site . Although it can be treated with BAE, the opening of the site of pancreatic duct anastomosis is often difficult to identify with BAE because it is small and scarred . Thus, the main pancreatic duct is dilated and punctured.…”
Section: Therapeutic Proceduresmentioning
confidence: 99%
“…16 Although it can be treated with BAE, the opening of the site of pancreatic duct anastomosis is often difficult to identify with BAE because it is small and scarred. 43 Thus, the main pancreatic duct is dilated and punctured. A guidewire is guided through the anastomotic site into the jejunum.…”
Section: Rendezvous Techniquementioning
confidence: 99%
“…Similarly, using a duodenoscope and performing bile duct cannulation and subsequent treatments are technically more difficult in patients with altered anatomy than in those with normal anatomy. A short‐type single‐balloon enteroscope, with a working length of 152 cm and working channel of 3.2‐mm, was developed to increase the number of devices that can be used during ERCP in patients with surgically altered gastrointestinal anatomy and was reported to be useful . However, selective biliary cannulation through the papilla is difficult in patients with surgically altered gastrointestinal anatomy than in those with normal anatomy because the appearance of the papilla is a reversal of its usual appearance in normal anatomy, the position is frequently tangential, and a forward‐viewing endoscope without an elevator is required.…”
Section: Introductionmentioning
confidence: 99%
“…A short-type single-balloon enteroscope, with a working length of 152 cm and working channel of 3.2-mm, was developed to increase the number of devices that can be used during ERCP in patients with surgically altered gastrointestinal anatomy and was reported to be useful. [1][2][3][4][5] However, selective biliary cannulation through the papilla is difficult in patients with surgically altered gastrointestinal anatomy than in those with normal anatomy because the appearance of the papilla is a reversal of its usual appearance in normal anatomy, the position is frequently tangential, and a forward-viewing endoscope without an elevator is required. Recently, the use of a pancreatic duct (PD) stent to facilitate selective biliary cannulation in patients with normal anatomy was described.…”
Section: Introductionmentioning
confidence: 99%